2000
DOI: 10.1007/pl00000639
|View full text |Cite
|
Sign up to set email alerts
|

Modification of glutamate receptors by phospholipase A2: its role in adaptive neural plasticity

Abstract: Long-term potentiation (LTP) and long-term depression (LTD) are two electrophysiological models that have been studied extensively in recent years as they may represent basic mechanisms in many neuronal networks to store certain types of information. In several brain regions, it has been shown that these two forms of synaptic plasticity require sufficient dendritic depolarization, with the amplitude of the calcium signal being crucial for the generation of either LTP or LTD. The rise in calcium concentration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…AA is regarded as a neuromodulator in the CNS, and PLA 2 is thought to have a role in neuronal plasticity (61). Neuronal excitation resulting from depolarization with high concentrations of potassium (62) and stimulation with excitatory neurotransmitter agonists such as ␣-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) (63), N-methyl-d-aspartic acid (NMDA) (64), and glutamate (65), as well as muscarinic cholinergic agonists (66), can stimulate AA release in neurons.…”
Section: Pla 2 In Neuronsmentioning
confidence: 99%
“…AA is regarded as a neuromodulator in the CNS, and PLA 2 is thought to have a role in neuronal plasticity (61). Neuronal excitation resulting from depolarization with high concentrations of potassium (62) and stimulation with excitatory neurotransmitter agonists such as ␣-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) (63), N-methyl-d-aspartic acid (NMDA) (64), and glutamate (65), as well as muscarinic cholinergic agonists (66), can stimulate AA release in neurons.…”
Section: Pla 2 In Neuronsmentioning
confidence: 99%
“…It has been proposed that during high frequency stimulation a large entry of calcium mediated by N-methyl-D-aspartate (NMDA) glutamate receptor activation might cause an increase in PLA 2 activity. The enzyme would augment AMPA receptor affinity by changing the lipid environment of AMPA receptors, thereby producing LTP (10). Recently, it has been reported that detergent-insoluble caveolin-rich membrane domains are markedly enriched in AMPA-type glutamate receptors (11), AA and PLA 2 (12,13), suggesting a possible role for PLA 2 in caveolae-dependent cellular functions.…”
mentioning
confidence: 99%
“…The activation of both isoforms of phospholipase A 2 is partly the mechanism mediating the change of properties of AMPA-sensitive glutamate receptors, playing an important role in the modulation of neurotransmission [29,30]. It is possible also to note the role of phospholipase A 2 in enhancing the secretion of neurotransmitters in the nervous system, mediated by independent of Ca 2+ liberation of fatty acids (especially arachidonic) from the PLs of the synaptic membranes, which initiates the fusion of the mediator vesicles with the acceptor [31].…”
Section: +mentioning
confidence: 99%